HUBUNGAN ANTARA INTENSITAS MENGIKUTI EKSTRAKURIKULER KEAGAMAAN DENGAN PERILAKU SOSIAL SISWA DI MAN 1 BUNGO - Disuwara, Gita; Kurniawan, Sugeng; Sabli, Muhammad; Baili; Yulia Friska, Sonia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Religious extracurricular activities in Islamic schools are normatively aimed at strengthening social ethics and peer group cohesion, yet their empirical impact on students’ social behavior remains associative and insufficiently measured across multiple dimensions. This study aimed to analyze the relationship between participation intensity in religious extracurricular activities and students’ social behavior, and to measure its predictive power. A quantitative correlational design was applied to 174 students of MAN 1 Kabupaten Bungo, selected via stratified random sampling. Instruments included standardized Likert scales for participation intensity (α = 0.86) and social behavior (α = 0.89), validated for construct validity (KMO = 0.812). Data were analyzed using prerequisite tests, Pearson correlation, and simple linear regression. Results indicated a significant positive relationship (r = 0.548; p < 0.001) with moderate strength. The regression model yielded R² = 0.300 (F = 73.41; p < 0.001), indicating that 30% of social behavior variance can be predicted by participation intensity. Discussion confirms that attendance frequency, duration of active involvement, and consistency of roles facilitate prosocial habituation through social learning mechanisms and peer modeling reinforcement. It is concluded that participation intensity in religious extracurricular activities significantly contributes to students’ social behavior formation. The study recommends optimizing collaborative project-based extracurricular designs, monitoring active participation, and integrating social behavior assessment into madrasah character development reports.